Seismic Pore Water Pressure Relief Wells for Gravel ColumnâBed System - Toha, Franciscus Xaverius (ITB Journal Publisher, LPPM ITB, 2017)
Liquefaction mitigation can be achieved by dissipating seismic pore pressures. The research reported in this paper elaborates the effectiveness in dissipating seismic pore pressures of a gravel bed and relief well system using gravel columns in a case study in Cilacap, Indonesia. Seismic pore pressure generation was analyzed using commonly available methods in liquefaction analysis. The evaluated pore pressures in the sand layer and gravel columns were used in a 2D dissipation analysis using finite-difference consolidation equation solutions. The results of this study showed that a simple and cost-effective relief well and gravel bed or strip system can effectively dissipate excess pore pressures in the sand layer and gravel columns to a maximum residual pore pressure below 40%, thus reducing liquefaction potential as well as protecting the foundations in the sand.